GRAMMAR INSTRUCTION AND THE ACQUISITION OF GUSTAR-TYPE VERBS BY ENGLISH-SPEAKING LEARNERS OF SPANISH - López Jiménez, María Dolores (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Spanish gustar-type verbs form part of a group called psych verbs (Belletti and Rizzi 1988). These verbs pose potential learnability problems for English-speaking learners of college-level Spanish since the most frequent and unmarked word order with gustar-constructions is OVS in contrast to the obligatory SVO pattern in English. This study addresses two questions: a) Does instruction promote the acquisition of gustar-type verbs? b) If so, are there task effects1 ? A total of 24 upper-level beginners (first year, second semester) of Spanish as an FL participated in this study: 12 formed part of the treatment group and 12 were included in the control group. Two threepart tests were administered in a 3-week period. The pre- and post-teaching tests consisted of a multiple-choice task, a scrambled sentences task and a free production task, and were distributed during the first and third week, respectively. Teaching which consisted of grammar explanation and practice took place the third day of class of the first week. A total of six days of class elapsed between both tests. Results indicated that the treatment group outperformed the control group in the scrambled sentences and the multiplechoice tasks, but not in the free production task in the post-teaching test. A task effect was found: production of target-like forms by both the experimental and control groups decreased as production became less controlled.